Silicon carbide and related materials 2017 : selected peer reviewed papers from the 2017 International Conference on Silicon Carbide and Related Materials (ICSCRM 2017), September 17-22, 2017, Washington, DC, USA - Stahlbush, Robert (Materials science forum, 2018)
This collection of papers by the results of the 2017 International Conference on Silicon Carbide and Related Materials (ICSCRM 2017, September 17-22 in Washington, DC, USA) presents for readers the latest progress in the field of development and production of silicon carbide semiconductors and their application in the power electronic devices. Silicon Carbide, Semiconductors, Bulk and Epitaxial Growth, Surface Defects, Properties, Processing, MOS and MOSFET Structures, Power Devices, Circuits, Applications Materials Science.